2012
DOI: 10.1002/pola.26113
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of graft terpolymers by addition reaction of amino‐terminated polyether to poly(methacrylate)s bearing five‐membered cyclic dithiocarbonate moieties and application of the graft terpolymers as modifiers for wool

Abstract: Graft terpolymers bearing polyether side chains and poly(methacrylate) stems were synthesized by the graft‐onto reaction of monoamino‐terminated poly(PO9‐co‐EO1) to poly{[5‐(methacryloyloxy)methyl‐1,3‐oxathiolane‐2‐thione]‐co‐n‐butyl methacrylate} [poly(DTCMMA‐co‐BuMA)]. The grafting reaction proceeded via the nucleophilic addition of the terminal amino groups to the five‐membered cyclic dithiocarbonate moieties giving thiol moieties, although the grafting efficiency was low (9–34%) due to the steric hindrance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…We first performed the homopolymerization of DTCMMA via free-radical polymerization; the homopolymers with a modest molecular weight showed extremely poor solubility in common solvents such as THF, DCM, anisole, toluene, ethyl acetate, and cyclopentanone. The solubility issue can be addressed by introducing a comonomer, as it was reported that a copolymer of DTCMMA and n BMA, namely, poly­(DTCMMA- r - n BMA), synthesized by free-radical polymerization, was soluble in common solvents, though dispersity was not well controlled ( Đ > 2.7 at a f DTCMMA of 0.3) . To access soluble copolymers of DTCMMA with narrow molecular weight distribution, we conducted the RAFT copolymerization of DTCMMA and n BMA in anisole.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We first performed the homopolymerization of DTCMMA via free-radical polymerization; the homopolymers with a modest molecular weight showed extremely poor solubility in common solvents such as THF, DCM, anisole, toluene, ethyl acetate, and cyclopentanone. The solubility issue can be addressed by introducing a comonomer, as it was reported that a copolymer of DTCMMA and n BMA, namely, poly­(DTCMMA- r - n BMA), synthesized by free-radical polymerization, was soluble in common solvents, though dispersity was not well controlled ( Đ > 2.7 at a f DTCMMA of 0.3) . To access soluble copolymers of DTCMMA with narrow molecular weight distribution, we conducted the RAFT copolymerization of DTCMMA and n BMA in anisole.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, the light-mediated thiol–ene click reaction shows high reaction efficiencies higher than 80%, , while our results exhibited a relatively low DF in the reaction. We first hypothesized that the basic reaction conditions coming from the amine reactant are responsible for the formation of disulfides, which reduce the thiol concentration and limit the reaction. This possibility was investigated with additional experiments in which the polymer film was treated with a DTT reducing agent that can break the disulfide bond before the start of the coupling reaction with AB.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a method to avoid the oxidative coupling of thiols, we reported one-pot reactions of in situ generated multiple thiols from dithiocarbonates and amines for fabrication of well-defined polymers [12,13]. This reaction giving thiols is a click reaction [12,13,14,15,16,17,18,19] selective enough to provide a polymer-bearing thiol moieties in the repeating units serving as a polymeric chain transfer agent [12] and dithiols for three-component polyaddition with quantitative atom-economy [13]. We applied this concept to this synthesis of organic-sulfur-zinc hybrid materials.…”
Section: Introductionmentioning
confidence: 99%